CONSERVATIVE MANAGEMENT OF MESH SITE INFECTION IN VENTRAL HERNIA REPAIR - Ahmad, Sajjad; Mufti, Tariq Saeed; Zafar, Arshad; Akbar, Ismail (Journal of Ayub Medical College Abbottabad, 2007)
Background: Mesh Hernioplasty is the preferred surgical procedure for abdominal wall hernias and infection remains one of the most common complications of this technique. In some patients the mesh may need removal to overcome infection, where as others may be salvaged by conservative treatment. This study was conducted to assess the outcome of conservative management for mesh site infection in abdominal wall hernia repairs. Methods: This study was carried out in Ayub Teaching Hospital Abbottabad Pakistan from Jan 2006 to Dec 2007. Thirteen consecutive cases were included, who developed mesh site infection after abdominal wall hernia repair. Pus or purulent fluid was sent for culture and sensitivity. All patients were treated by intravenous antibiotics and local wound care. Treatment was taken as successful when there was complete resolution of infection and healing of the wound. Results: There were 7 inguinal (53.84%), 4 para-umbilical (30.76%) and 2 incisional hernias (15.38%). Eight patients were males (61.53%) and 5 females (38.46%). Median age of the patients was 40 years (range 28 to 52 years). Staphylococcus aureus was the most commonly found organism causing infection in 8 patients, (76.9%). Mean hospital stay was 22 days (range 18-26 days). All cases were effectively treated conservatively without removing the mesh. Polypropylene mesh was used in all of these cases. Conclusion: Conservative management is likely to be successful in mesh site infection in abdominal wall hernia repairs. Key words: Abdominal hernia, Mesh, Infection